Analisis Konten Budaya dalam Buku Ajar BIPA "Ramah Berbahasa Jilid I" bagi Penutur Arab - Fauzan, Fauzan; Albantani, Azkia Muharom; Arifin, Fatkhul; Umbar, Kisno (Arabi : Journal of Arabic Studies, 2023)
This research is aimed at examining the BIPA teaching book "Language Friendly Volume 1" published by Antasari Banjarmasin State Islamic University from several aspects: First, a review of the suitability of the material with the Graduate Competency Standards (SKL) stipulated in the Permendikbub from its accuracy and cultural content. Second, this research is aimed at examining the suitability of material for Arabic speakers, this refers to the fact that Arabs often dominate BIPA participants at UIN Antasari. This study uses a qualitative approach because the data are in the form of narratives or text. The method used by researchers is content analysis. The indicators used in analyzing the book's content were adopted from Muslich, and the rating interval was adopted from the scale developed by Nurgiyantoro. The results of this study revealed that the BIPA textbook "Language Friendly Volume 1" designed for the A1 level of need, was still "not appropriate" with a percentage of 50%. The drawback is that the author is inconsistent in presenting the material, narrative, dialogue, and Indonesian insights. There is also material content that is not yet time to be delivered at the A1 level. This BIPA textbook is considered not suitable for use by Arabic speakers or even other foreign speakers.